Asymmetric total synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Harale, Kishor R.; Kalkote, Uttam R. (Tetrahedron Letters, 2011)
A synthetic route to (2S,3S)-3-hydroxypipecolic acid was achieved from readily available nonchiral pool starting material cis-2-butene-1,4-diol and involved Claisen orthoester rearrangement, Sharpless asymmetric dihydroxylation and intramolecular lactamisation of azido lactone as the key steps. (C) 2010 Elsevier Ltd. All rights reserved.

Convenient formal synthesis of (2S,3S)-3-hydroxy pipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Dumare, Nilesh B.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2011)
A convenient synthesis of (2S,3S)-3-hydroxy pipecolic acid starting from inexpensive and easily available L-(+)-tartaric acid has been described. (C) 2011 Elsevier Ltd. All rights reserved.

Formal synthesis of (-)-stemoamide using a useful epimerization at C-8 - Chavan, Subhash P.; Harale, Kishor R.; Puranik, Vedavati G.; Gawade, Rupesh L. (Tetrahedron Letters, 2012)
The formal synthesis of (-)-stemoamide was achieved starting from L-pyroglutamic acid. The key steps used are the allylation using BF3 center dot OEt2, ring closing metathesis, allylic oxidation and a novel epimerization at C8. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Allylation; Allylic oxidation; Pyroglutamic acid; Ring closing metathesis; Stemoamide

Very practical and selective method for PMB protection of alcohols - Chavan, Subhash P.; Harale, Kishor R. (Tetrahedron Letters, 2012)
A very simple, practical and efficient one-step heterogeneous protocol for the PMB protection of alcohols using Amberlyst-15 has been developed. The stability and hazard issues regarding PMBCI and PMBBr are totally avoided by directly using anisyl alcohol for the protection. Alcohols are protected in very good yields. The selective mono-PMB protection of diols as well as di-PMB protection of diols was achieved in good yields, along with the demonstration of recyclability of the catalyst. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 4-Methoxybenzyl alcohol; 4-Methoxybenzyl protection; Amberlyst-15; Di-PMB protection; Mono-PMB protection

Short synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Pawar, Kailash P. (Tetrahedron Letters, 2013)
A convenient synthesis of (2S,3S)-3-hydroxypipecolic acid starting from cheap and abundant L-(+)-tartaric acid has been achieved. The strategy employs selective ester reduction and reductive lactamization as key steps. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reductive lactamization; Selective deprotection; Wittig reaction